Nitrogen Fertilizer Sources: What does the future hold for citrus producers? - Thomas Obreza; Larry Parsons; Kelly Morgan (EDIS, 2009)
Revised! SL-238, a 4-page fact sheet by Thomas Obreza, Larry Parsons, and Kelly Morgan, discusses the factors influencing the price of nitrogen fertilizer sources and economic considerations for future nitrogen fertilizer availability. Published by the UF Department of Soil and Water Sciences, February 2009.